Host biology and genomic properties of Plumeria mosaic virus, a tobamovirus discovered in a temple tree in India co-infecting with frangipani mosaic virus - Kumar, Alok; Solanki, Vikas; Katiyar, Akshay; Mandal, Bikash (Frontiers in Microbiology, 2022)
Temple tree (Plumeria rubra f. acutifolia), an important fragrant-flower tree extensively used in the urban landscaping is known to be infected with a tobamovirus, frangipani mosaic virus (FrMV). In this study, we describe another tobamovirus, Plumeria mosaic virus (PluMV) infecting temple tree in India. PluMV was isolated from an old temple tree co-infected with FrMV. The presence of another tobamovirus was initially realized based on the distinct symptoms on Gomphrena globosa (globe amaranth), a non-host of FrMV. PluMV was highly transmissible through simple rub-inoculation. In host-range study, brinjal (Solanum melongena), chilli (Capsicum annuum), datura (Datura stramonium), globe amaranth (G. globosa) and tobacco (Nicotiana benthamiana, N. glutinosa, N. tabacum cv. Xanthi) could differentiate PluMV from FrMV. The complete genome sequence of PluMV was determined (6688 nucleotides [nt], GenBank KJ395757), which showed the genome structure typical of tobamovirus encoding four proteins: small replicase (3549 nt/130 kDa), large replicase (5061 nt/188 kDa), movement protein (770 nt/29 kDa) and coat protein (527 nt/19 kDa). The 5′ and 3′ UTR of PluMV contained 91 and 284 nt, respectively. The PluMV genome was 45 nts longer than that of FrMV and shared only 71.4-71.6% sequence identity with FrMV and <50% sequence identity with the rest of the other members of the genus Tobamovirus. PluMV shared a close but a divergent evolutionary relationship with FrMV. Based on the species demarcation guidelines of ICTV (<90% genome sequence identity), PluMV was considered as a new tobamovirus species. As PluMV was serologically related with FrMV, differential diagnostic assays such as simplex and duplex RT-PCR were developed, which revealed that PluMV naturally existed in both the species of temple tree, P. rubra f. acutifolia and P. rubra f. obtuse in India either alone or in mixed infection with FrMV.